Stented Coronary Artery Phantom for Particle Image Velocimetry - Chu, Boby; Mongrain, Rosaire; Leask, Richard; Bertrand, Olivier F. (CMBES Proceedings, 2007)
rregular inner surfaces of a stented blood vessel can cause blood perturbations that have physiological and perhaps pathological consequences. T o study these flow perturbations, a new 3D geometrically correct scaled up cylindrical phantom was developed for use in conjunction with an optically clear blood analog and particle imagery velocimetry.